2004
DOI: 10.1063/1.1756220
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering and photoluminescence of As ion-implanted ZnO single crystal

Abstract: We have converted the surface of undoped ZnO bulk into the As-doped p-ZnO layer by means of the As ion implantation method. After postimplantation annealing, the As-related properties were investigated by using Raman scattering and photoluminescence (PL) experiments. The Raman spectrum shows that the E2high peak obtained from the As-doped p-ZnO shifted toward the higher energy side of 0.55 cm−1 in comparison with that of the undoped ZnO bulk. This result is related to the stress increment of the sample surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(38 citation statements)
references
References 14 publications
4
34
0
Order By: Relevance
“…5 that how Cu-doping influence the E 2 (high) mode of ZnO. The E 2 (high) is known to be the band characteristic of the wurtzite phase [26]. As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…5 that how Cu-doping influence the E 2 (high) mode of ZnO. The E 2 (high) is known to be the band characteristic of the wurtzite phase [26]. As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, the report on the stimulated emission from optically pumped ZnO polycrystalline thin films at room temperature 8,9 has attracted considerable attention to the studies of optoelectronic properties of ZnO films. There are several reports on the studies of photoluminescence (PL) [10][11][12][13][14][15][16] and photoconductivity (PC) properties of ZnO films, [17][18][19][20][21][22] which are mainly focused either on the emission or on the UV photoresponse properties. It has been found that factors such as film thickness and grain size, 23 crystallographic orientation, 24 postdeposition annealing temperature and ambient, 19 doping effect with nitrogen, 25 presence of micropores, 23 and encapsulating layer 19 influence the emissions as well as photoresponse characteristics of ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of these As-related emissions means that the surface of the undoped ZnO was converted into the As-doped p-type ZnO layer by the As ion implantation process. In addition, by the measuring current-voltage characteristic curve, we verified that the interface between implanted surface and substrate was made up of the p-n junction [11].…”
Section: Optical Properties Of As-implanted Zno Layermentioning
confidence: 99%